Composición química del compost en sistema abierto con sustratos de estiércol y rastrojo vegetal en el CIEY, Km17, Yurimaguas - Diaz Huaynacari, Gloria Stefani (2025)
The study was carried out at the Yurimaguas Km 17 Research and Teaching Center, of the National University of the Peruvian Amazon (CIEY- Km 17- UNAP). The objective was to evaluate the chemical composition of compost in an open system with manure and plant stubble substrates at the CIEY, Km 17, Yurimaguas. Using a Completely Randomized Block Design with 4 treatments and 4 repetitions. The treatments were: T1: black earth; T2: cowshed + kudzu stubble; T3: sheep pasture + kudzu stubble and T4: cow pasture + kudzu stubble. The experimental phase lasted 6 months. Regarding the chemical properties, the following values were obtained in the hydrogen potential: T1 (5.34); T2 (8.21); T3 (8.77) and T4 (8.47); in the C/N ratio it was achieved in T1 (11.55%); T2 (12.94%); T3 (12.94%) and T4 (12.93); in the OM content it was obtained in T1 (3.88%); T2 (48.33%); T3 (40.96%) and T4 (50.44%). The nitrogen content was: T1 (0.20%); T2 (2.17%); T3 (1.84%) and T4 (2.49%); in the phosphorus content it was achieved: T1 (0.00073%); T2 (0.00642%); T3 (0.00672%) and T4 (0.00743%) and the potassium content was obtained: T1 (0.011%); T2 (0.863%) %); T3 (1,073%) and T4 (1,379%). According to the results obtained, the following conclusions were determined: compost was obtained technically. Significant statistical differences were found when evaluating the physicochemical properties and nutritional quality of the compost. The values of hydrogen potential, C/N ratio, organic matter and potassium were shown in a similar way; while the values of nitrogen and phosphorus were not similar. In general terms, the best treatment in the present research work was in T4, consisting of guinea pig manure + kudzu stubble, with better values in nitrogen, phosphorus, potassium content, in addition to pH and organic matter.